Rabies outbreak in Greece during 2012–2014: use of Geographical Information System for analysis, risk assessment and control - Giannakopoulos, A.; Valiakos, G.; Papaspyropoulos, K.; Dougas, G.; Korou, L. M.; Tasioudi, K. E.; Fthenakis, G. C.; Hutchings, M. R.; Kaimaras, D.; Tsokana, C. N.; Iliadou, P.; Spyrou, V.; et al. (Cambridge University Press, 2016)
The objectives of this work were (i) geographical analysis of the 2012–2014 outbreak of rabies in Greece using GIS and (ii) comparative analysis of animal cases with data of potential human exposure to rabies together with environmental data, in order to provide information for risk assessment, effective monitoring and control. Most animal cases (40/48) involved red foxes, while domestic animals were also diagnosed with rabies. Overall, 80% of the cases were diagnosed in central northern Greece; 75% of the cases were diagnosed in low altitudes (<343·5 m), within a distance of 1 km from human settlements. Median distance from livestock farms was 201·25 m. Most people potentially exposed to rabies (889/1060) presented with dog bite injuries. Maximum entropy analysis revealed that distance from farms contributed the highest percentage in defining environmental niche profiles for rabid foxes. Oral vaccination programmes were implemented in 24 administrative units of the country during 2013 and 2014, covering a total surface area of ~60 000 km2. Rabies re-occurrence in Greece emphasizes the need for ongoing surveillance in cross-border areas and in areas with intense human activity.